A coupled thermomechanical approach for finite element forming simulation of continuously fiber-reinforced semi-crystalline thermoplastics. (October 2019) - Dörr, Dominik; Joppich, Tobias; Kugele, Daniel; Henning, Frank; Kärger, Luise
Abstract: A coupled thermomechanical approach for macroscopic Finite Element (FE) thermoforming simulation of continuously fiber-reinforced semi-crystalline thermoplastic, which is implemented in the commercial FE solver Abaqus in combination with several user-subroutines, is presented. Thermal modeling takes into account radiation, convection and heat conduction as well as the prediction of recrystallization during forming. Mechanical behavior is modeled layer-by-layer and takes into account rate-dependent forming behavior by means of hyperviscoelastic constitutive equations following a nonlinear generalized Maxwell approach. The phase transition is considered in material modeling by coupling the mechanical properties to the temperature and the degree of crystallinity. In application of the presented thermomechanical approach to a generic geometry, an improved agreement of forming simulation to experimental results is observed against a purely isothermal approach. Thereby, some defects are only predicted by the thermomechanical approach, which makes a coupled thermomechanical approach considering temperature and crystallization kinetics favorable for the virtual process design.